Commissioning new applications on processing machines: Part I - process modelling - Troll, Clemens; Schebitz, Benno; Majschak, Jens-Peter; Döring, Michael; Holowenko, Olaf; Ihlenfeldt, Steffen (Advances in mechanical engineering, 2018)
The subject of this splitted article is the commissioning of a new application that may be part of a processing machine. Considering the example of the intermittent transport of small-sized goods, for example, chocolate bars, ideas for increasing the maximum performance are discussed. Starting from an analysis, disadvantages of a conventional motion approach are discussed, and thus, a new motion approach is presented. For realising this new motion approach, a virtual process model has to be built, which is the subject of this article. Therefore, the real process has to be abstracted, so only the main elements take attention in the modelling process. Following, important model parameters are determined and verified using virtual experiments. This finally leads to the possibility to calculate useful operating speed–dependent trajectories using the process model.